2012
DOI: 10.1093/humrep/des051
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic non-disjunction mechanisms in human fertile males

Abstract: background: In humans, little is known about the mechanisms of non-disjunction working in male meiosis, although considerable attention has been given to these mechanisms in female meiosis. The present study explores the origin of meiotic non-disjunction during human spermatogenesis and the chromosomes most commonly involved in this process. methods:We used Multiplex fluorescence in situ hybridization to carry out meiotic analyses in metaphase I (MI) and metaphase II (MII) spermatocytes from three fertile dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
3
12
0
1
Order By: Relevance
“…48). Trisomy 21 pregnancies (95%) are due to errors in female meiosis 48 , whereas errors in chromosome segregation in male meiosis are much lower, being around 2.5% for autosomes 49 . Unlike meiotic divisions in males, which take place immediately after pachytene and successful recombination, female meiosis comes to a halt for weeks or months (in mice) or decades (in humans) in prophase I, before meiosis is resumed to give rise to one or more fertilizable eggs.…”
Section: Discussionmentioning
confidence: 99%
“…48). Trisomy 21 pregnancies (95%) are due to errors in female meiosis 48 , whereas errors in chromosome segregation in male meiosis are much lower, being around 2.5% for autosomes 49 . Unlike meiotic divisions in males, which take place immediately after pachytene and successful recombination, female meiosis comes to a halt for weeks or months (in mice) or decades (in humans) in prophase I, before meiosis is resumed to give rise to one or more fertilizable eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated such a frequency at 2.31%, while three other cases of three-way CCR analyses found it to be 9.3% (Loup et al 2010), 3.15% (Pellestor et al 2011b) and 15.6% (Godo et al 2013). Unexpected FISH phenotypes can be the consequence of three factors: i) nondisjunction at the second meiotic division, ii) increasing difficulty in FISH result interpretation with increasing number of chromosomes involved, and iii) possible chiasma occurrence, leading to the formation of additional recombinant chromosomes (Anton et al 2007, Uroz & Templado 2012. In cases of three-way der (6) der (10) 10 6 11 der (11) q25.1 q24.3 q23.1 Figure 3 Schematic model of the suggested hexavalent configuration during the pachytene stage in meiosis I in a 46,XY,t(6;10;11)(q25.1;q24.3;q23.1)mat carrier.…”
Section: Discussionmentioning
confidence: 92%
“…Studies conducted to date have shown that the overall disomy frequencies observed in spermatocytes II are significantly higher than those observed in mature human spermatozoa, suggesting the existence of effective, post‐meiotic checkpoint mechanisms that monitor and arrest spermatocytes II with numerical abnormalities. Inefficient control mechanisms could, therefore, be one explanation for the increased rate of chromosome abnormalities observed in the spermatozoa of certain male subgroups (Uroz & Templado, ).…”
Section: Resultsmentioning
confidence: 99%